AN OVERVIEW OF FAMILY FOOD SECURITY DURING THE COVID-19 PANDEMIC IN ACEH PROVINCE - Fandila, Bella; Ahmad, Aripin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: Coronavirus is a new type of virus that has been found in humans, first reported in Wuhan China, in December 2019. In Indonesia as of August 18, 2021, there were 3.908.247 confirmed positive case, 121.141 deaths and 3.443.903 recoveries. In Aceh, there were 37.797 confirmed case, 1.707 in treatment, 34.148 recovered cases and 1.937 deaths. Methods: This research is descriptive in nature to see a picture of family food security during the Covid 19 pandemic. A sample of 70 people, was carried out in total population. Result: The results of the data on the frequency distribution of family food security during the Coid-19 pandemic in Aceh Province showed that in the last 4 weeks there were worries that there was not enough food in the household (55.7%), never in the household could not eat the preferred type of food due to lack of resources (75.7%), never household members felt limited to eating various types of food due to lack of resources (80.0%), never had a household members eat food that they didn't want to eat because of limited resources to get other types of food (85.7%), never mothers or other family members ate small portions for fear of not having enough for other family members (88.6%), there was once a family member who ate less food in a day because there was not enough food (90.0%), never in the household did not have food supplies to eat due to lack of resources to get food (91.4%), never had any family member sleep at night hungry because there is not enough food (97.1%), there has never been any family member who went from morning to night without eating anything because they felt there was not enough food (97.1%). Recommendation: It is hoped that through the role of nutritionists in providing media containing information about family food security in order to increase the knowledge of the population in Aceh Province regarding family food security.